Experimental investigation of effects of linear heat input on microstructures and strength in 316 stainless fabricated by directed energy deposition - Wang, Yingjie (Nanyang Technological University, 2021)
Additive Manufacturing (AM) technology has been growing rapidly over the past decade, leading to its widespread use in today’s manufacturing industry. One of the most common AM techniques used to manufacture metal components is Directed Energy Deposition (DED). In this project, systemic investigation on microstructure evolution and mechanical properties of 316L stainless steel (SS) manufactured via DED was conducted. Microstructure characterization using optical microscopy (OM) and scanning electron microscopy (SEM) shows that finer microstructures, such as smaller grain size and cell size, evolve in blocks manufactured with lower linear heat input and increase monotonically with increasing linear heat input, which is resulted from reduced cooling rate with increasing heat input. The volume fraction of porosity first decreases with increasing linear heat in the range of 66-96 J/mm, then increases with increasing linear heat input. Mechanical tests on different blocks show that both hardness and strength of as-built blocks reduce with increasing linear heat input and an opposite trend is identified in ductility, which is resulted from variation in microstructures with various linear heat input. The results obtained show that linear heat input plays a critical role in microstructure evolution and therefore mechanical properties.